DEIXIS IN JUSTIN BIEBER’S SONGS - Nopika Adelina Ginting; Chaidir Syahri (PROJECT (Professional Journal of English Education), 2021)
This research entitled Deixis in Justin Bieber’s Songs. The aims of this research is to analyze kind of deixis that used of Justin Bieber’s song lyrics in ‘Purpose Album and dominant deixis that used in this song. The focus types deixis which analyzed are: person dexis, place deixis and time deixis.The data used to complete this study is song lyrics of Justin Bieber in ‘Purpose Album. The song lyrics data got from internet browsing. Descriptive qualitative design is used to conduct this research. Having analyzed the data, the findings of this study are: (a) There are three kinds deixis are found, namely: person deixis (you,I, we, it, me, us, your, myself, yourself), time deixis (all day, all night, then, when, once, twice, tonight, at second chance, all the times, night, and place deixis (in this game, in my work, on my own); (b) The deixis words to be analyzed are 145 words; 130 words are person deixis, 11 words are time deixis, 4 words are place deixis; (c) The dominantly deixis that found is person deixis are 130 words or 89,6%. The researcher proposes student should learn deixis from song lyrics, because it’s familiar in society.  Keywords:  Deixis, Song Lyric, Place Deixis, Time Deixis, Person Deixis